Speak like a CEO : secrets for commanding attention and getting results - Bates, Suzanne (McGraw-Hill Education, 2018)
An award-winning news anchor presents methods for better communication in any business environment During her 20 years in broadcasting, award-winning news anchor Suzanne Bates conducted more than 10,000 interviews, during which she witnessed business leaders, politicians, and celebrities at their best and worst. Now a top CEO communication coach, Bates is renowned for her uncanny ability to transform even the shyest oratorical mouse into a public-speaking lion. In Speak Like a CEO, Bates: Reveals the secrets for communicating in any situation Describes simple techniques for acing speeches, presentations, media interviews, Q & A sessions, business meetings, and more Outlines self-improvement plans that can easily be customized to your needs Shares secrets from top leaders, including Mario Cuomo's technique for overcoming stage fright and Colin Powell's secret for projecting authenticity.